Perbaikan Sistem Daya Apung Perahu Fiberglass Guna Meningkatkan Keselamatan Operasi Budidaya Rumput Laut Di Kabupaten Jeneponto - Wahyuddin Mustafa (Faculty of Engineering UNHAS, 2020)
The population of Pattontongan area, Biringkassi village, Binamu district, Jeneponto regency are generally working as fishermen and seaweed cultivators. The fishermen and farmers are commonly form a group for their activities. One of the group is called Pattontongan City. Each group member is manage seaweed with an area of ½ hectare. They use small boats which are made of wood and fiberglass in carrying out their activities. The characteristics of their boat including the fiberglass boats are; the proportion of the boat length and width is big, while the proportion of the boat width and height is small. Hence the boat stability is not good and must be equipped with outrigger to keep the boat stable. Fiberglass boat hulls are constructed without frames while the thickness of the hull is relatively thin. The boats are also equipped with empty tanks (void tanks) as a buoyancy system. During field visit, it was found that the void tanks as the boat bouyancy system did not work as expected as they apply small 10 mm diameter of hole in the tanks. The hole will put the boat at the risk of being sinking. The solution offered in order to keep the production process and operation of seaweed farming can still workable is by reducing or omitting the chance of the boat to sink. This can be done by improving the boat buoyancy reserve system. The solution is being introduced and taught to the fishermen and farmers. The results shows that the fishermen and the farmers are understand the importance of the boat bouyancy reserve system and that that the repairing action to the boat void tanks using the hand lay-up method and hence improving the bouyancy reserved system can be easily absorbed by them.